Mitochondrial DNA: A Molecular Tool for Assessment of Genetic Diversity - Mohapatra, Sunil Kumar; Nayak, Vivek Kumar; Paul, Abhishek; Adhikary, Sudip (International Journal of Livestock Research, 2019)
The most important component of any breed improvement programme is genetic diversity which is the major cause of genetic gain. Assessment of population structure and genetic diversity is a basic tool for genetic improvement. The decline in genetic diversity results in inbreeding and consequent reduction in the performance. Significant morphological differences exist among various breeds but little information is available on their genetic diversity and structure. So, it is more important to access the genetic diversity of a population. There are various ways to access genetic diversity and structure of the population and studying mitochondrial DNA diversity is one of them. Mitochondrial DNA with unique features of maternal inheritance, a relatively fast rate of evolution and lack of recombination has proved to be useful markers for assessment of genetic diversity. Hence the current review aims to discuss the importance of mtDNA for the assessment of genetic diversity.